Symposium 2: Inequality as Higher Education Goes Online - Czerniewicz, Laura (Proceedings of the International Conference on Networked Learning, 2016)
This paper discusses Higher Education (HE) and changes in HE, using inequality as a frame. It provides an brief overview of the changes in the HE landscape; explains how Therborn’s 2013 equality/inequality is framework suitable for this discussion ; considers some of the key questions and implications at the global, institutional and course levels through this inequality lens; and finally asks some questions and make some suggestions for how the issues of inequality in HE could be addressed going forward.